Assessing the impact of policy research and capacity building by IFPRI in Malawi - Ryan, James G. (International Food Policy Research Institute, 1999)
This study examines the contributions of IFPRI over the last 10 years to policy development, training, and capacity-strengthening activities with Malawi, focused particularly on addressing the chronic food insecurity and malnutrition that has prevailed for the last 60 years.The paper is divided into five sections. The first describes the range of activities with which IFPRI was involved: the extensive IFPRI/Cornell food security and nutrition monitoring phase, primarily with the Ministry of Agriculture and Livestock Development of Malawi, from 1989 to 1992; the analytical and capacity-building phase from 1992 to 1996, when IFPRI staff were located at the Bunda College of Agriculture of the University of Malawi; and the collaborative research phase, which began in 1996, and is still underway. The second section contains the results of extensive interviews, which the author had with IFPRI’s partners and stakeholders to elicit their perceptions of the value, influence, and impact of IFPRI in Malawi. This includes training, capacity strengthening,and policy research activities. The third section of the paper attempts to describe the more tangible indicators of IFPRI’s direct and indirect impacts in Malawi. The fourth section highlights some implications and lessons for IFPRI from the study of their impact in Malawi. The final section draws some conclusions.